A Call for a More Robust Word in Word and Sacrament. Issue 1 (April 2022) - Davis, David
The relationship of word and sacrament rests at the very core of a Reformed theology of worship. However, the fundamental inseparability of the two has struggled to find balance within the practice of worship and preaching in congregational life. The last 50 years has seen a significant increase in sacrament practice within the Presbyterian Church. The effort has largely been sparked by the desire to establish a better theological balance of word and sacrament consistent with the ecumenical world church. During that same period, however, preaching's engagement with the church's sacramental life has not been well served by the discipline of homiletics. The teaching of preaching has significantly ignored the theological depth and rich imagery of baptism and communion. It is time to call for a more vibrant engagement with the word on the occasions when the sacraments are being celebrated. This essay offers an exploration of how the preacher can live into relatively recent liturgical change that elevates sacramental practice while honoring the Reformed theological heritage of word and sacrament.